A LEGAL POSITION OF BUYING BINDING AGREEMENT WHICH PAYMENT IS MADE IN STAGES WHICH HAS BEEN CANCELED BY THE SUPREME COURT (STUDY OF SUPREME COURT DECISION NUMBER: 1650 K/PDT/2015) - Erizon Khairunsyah; Hasim Purba; Sunarmi; Rosnidar Sembiring (LPPM Universitas HKBP Nommensen, 2021)
In general, the implementation of the binding sale and purchase agreement is carried out using an authentic deed made before an authorized public official, namely a notary. The implementation of the sale and purchase binding agreement does not always run smoothly, sometimes there are factors that make the binding deed unable to continue and even cause the deed to be canceled. One of the factors that caused the sale and purchase agreement to be canceled was due to a default as can be seen in the decision of the Supreme Court Number: 1650 K/pdt/2015. The defendant did not pay the third stage of payment for the object of sale and purchase, as previously agreed in the deed of binding sale and purchase agreement. As a result, the judge canceled the PPJB Deed and the payment for stage one and stage two which had previously been paid by the defendant to the plaintiff then became the right of the plaintiff and could not be reclaimed.